Quantifying counterfactual military history - Fagan, Brennen; Horwood, Ian 1957-; MacKay, Niall J.; Price, Christopher G.; Wood, A. Jamie (CRC Press, Taylor & Francis Group, 2023)
"Forces shaping human history are complex, but the course of history is undeniably changed on many occasions by conscious acts. These may be premeditated or responsive, calmly calculated or performed under great pressure. They may also be considered to be successful or catastrophic, but how are historians to make such judgments and appeal to evidence in support of their conclusions? Further, and crucially, how exactly are we to distinguish probable unrealized alternatives from improbable ones? This book describes some of the modern statistical techniques that can begin to answer this question, as well as some of the difficulties in doing so. Using simple, well-quantified cases drawn from military history, we claim that statistics can now help us to navigate the near-truths, the envelope around the events with which any meaningful historical analysis must deal, and to quantify the basis of such analysis. Quantifying Counterfactual Military History is intended for a general audience who are interested in learning more about statistical methods both in military history and for wider applications"--
Keywords: Imaginary wars and battles; Military art and science / Decision making / Mathematical models; Combat / Mathematical models; Military history / Methodology; Counterfactual histories